Entrepreneurial success through learning, capital, and work engagement: Market and service orientation perspective - Sohail Ahmad; Qingyu Zhang; Muhammad Ali Hussain; Shahid Mahmood (Acta Psychologica, 2025)
Entrepreneurial success is determined by combination of cognitive, behavioral, and strategic factors, yet the relationship of these elements remains underexplored, particularly in dynamic market environments and emerging economies. This study examines how entrepreneurial learning intensity, psychological capital, and entrepreneurial work engagement drive success, mediated by market and service orientation, and moderated by digitalization. Based on resource-based view and psychological capital theory, the study suggests an integrated conceptual framework tested through survey data from entrepreneurial ventures. Data was collected through questionnaire surveyfrom chief executive officers of entrepreneurial ventures in China and Pakistan and analyzed through partial least square-structure equation modeling. Findings reveal that learning intensity and psychological resources significantly enhance success, with market and service orientation serving as important mediators. Digitalization further strengthens these relationships, highlighting its role as a strategic enabler. The study contributes to theory by bridging psychological and strategic perspectives, while offering practical insights for fostering resilient, customer-centric endeavors in evolving digital landscapes.